The genus Bactra Stephens (Lepidoptera Tortricidae) in the habitat of Cyperus rotundus L. in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors studied the existing relationship between the gen. Bactra species and the purple nutsedge (Cyperus rotundus L.).In Italy, to date, five species of Bactra: furfurana (Hawort), lancealana (Hübner), robustana (Cristoph), venosana (Zeller), bactrana Kennel, have been reported. The first four had already been known. The fifth was discovered by the Authors in 1979. The biology of Tortricidae and their area of distribution has already been illustrated. The larva of Bactra spp. causes damage, often very serious, to the purple nutsedge plant, undermining the base of the leaf sheath which result in the leaves becoming limp and dying and falling off. The bulb can also be attacked but never totally destroyed, whereas, the subsoil tuber remains undamaged.The spring generation of the Bactra spp. is very sparce whilst the summer flowering is very profuse.Trials, utilizing phytophagous, have been carried out in the fight against the Ciperacea, in various parts of the world. Techniques of grown colonies of  phytophagous were examined and results were obtained, which haven't been completely satisfactory, up to date. Other solutions have been tried, but they too, have not been very successful in eliminating the pests but they have, however, been able to limit the invasion, for a period, sufficient to allow the cycle growth of vegetables and other small needs and trees to be completed.
Keywords: Lepidoptera Tortricidae; Bactra spp.; Cyperus rotundus